(untitled) (Revista de Ciências Agroveterinárias, 2013)
Cellulose industry generates alkaline residues which must be characterized in order to evaluate the technical viability of their use in agricultural soils as an alternative of soil acidity correction. The objectives of this study were to evaluate the effect of the application of alkaline residue on some chemical and physical properties of a Humic Cambisol and on the initial growth phase of a wheat crop. The treatments consisted in doses of lime corresponding to 0.5 and 1 SMP and doses of residue corresponding to 0.25, 0.5 and 1 SMP in order to increase pH up to 6.0. The wheat was sown in 4 L pots filled with soil. The pots were arranged in a greenhouse according to a completely randomized experimental design with four replicates. The addition of Res increased soil pH, the sodium content and soil sodium saturation and reduced the clay flocculation. However, the stability of soil aggregates was not affected. Both correctives increased the soil’s basic cations, although the residue increased the Ca/Mg ratio. This alkaline residue is an alternative to correct acid soils and improve the chemical conditions of soils to grow wheat.